A simple low cost latent fingerprint sensor based on deflectometry and WFT analysis. (1st February 2018) - Dhanotia, Jitendra; Chatterjee, Amit; Bhatia, Vimal; Prakash, Shashi
Highlights: The latent fingerprint profiling is undertaken using deflectometric principle. 2D and 3D shape reconstruction of fingerprint is performed by using WFT algorithm. Very simple, inexpensive and robust design of experimental setup. Abstract: In criminal investigations, latent fingerprints are one of the most significant forms of evidence and most commonly used forensic investigation tool worldwide. The existing non-contact latent fingerprint detection systems are bulky, expensive and require environment which is shock and vibration resistant, thereby limiting their usability outside the laboratory. In this article, a compact, full field, low cost technique for profiling of fingerprints using deflectometry is proposed. Using inexpensive mobile phone screen based structured illumination, and windowed Fourier transform (WFT) based phase retrieval mechanism, the 2D and 3D phase plots reconstruct the profile information of the fingerprint. The phase information is also used to confirm a match between two fingerprints in real time. Since the proposed technique is non-interferometric, the measurements are least affected by environmental perturbations. Using the proposed technique, a portable sensor capable of field deployment has been realized.